Neurological Disorders Caused by Spine Myeloid Sarcoma - Kajal, Shah; Harsha , Panchal; Apurva, Patel; Chinmay , .; Sonia, Parikh (Current Overview on Disease and Health Research Vol. 1, 2022)
Myeloid sarcoma (MS) is a malignant extramedullary tumor made up of immature myeloid cells. It may occur before, concurrently with, or after acute myeloid leukemia (AML) in a de novo instance, or it may be present and the only symptom of recurrent AML, myelodysplastic syndrome, or chronic myeloid leukemia. The skin, orbit, bone, periosteum, lymph nodes, gastrointestinal tract, soft tissue, central nervous system, and testis are all frequently affected. MS is a difficult diagnosis to make because of its many symptoms and localisation, as well as the lack of a diagnostic protocol. This is especially true in patients who do not have initial bone marrow involvement. The precise diagnosis of MS is critical for optimal treatment, which is frequently delayed due to a high risk of misdiagnosis. We presented three examples of MS derived from the spine, each with back pain, paraplegia, and paraparesis, as well as a review of the literature. A larger number of patients in a multinational trial are needed to completely understand the characteristics of isolated MS and to develop novel and targeted treatments.